Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3109/14764172.2011.564769
|View full text |Cite
|
Sign up to set email alerts
|

308-nm Excimer laser treatment of palmoplantar psoriasis

Abstract: Psoriasis is a chronic inflammatory condition affecting 1-3% of the population. The incidence of palmoplantar involvement has been estimated to be between 2.8% and 40.9%. Significant psychosocial distress and difficulty performing activities of daily living can result. Treatment is often challenging. Traditional treatments include topical steroids, anthralin, calcipotriene, PUVA, methotrexate, cyclosporine, retinoids and biologics. In this case series, we report our success with the 308-nm excimer laser in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Since the publication of the Cochrane review, nine open studies on PPPP treatment have been published. [5][6][7][8][9][10][11][12][13] None was performed vs. placebo.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the publication of the Cochrane review, nine open studies on PPPP treatment have been published. [5][6][7][8][9][10][11][12][13] None was performed vs. placebo.…”
Section: Methodsmentioning
confidence: 99%
“…Five prospective studies, [9][10][11][12][13] all with a level of evidence of 3, assessed Laser Excimer UVB-NB (Excimer 308 nm) in PPPP. The combined analysis of these studies showed that 64% of patients experienced an improvement of 70% at the end of treatment (Fig.…”
Section: (Level 3)mentioning
confidence: 99%
“…Twenty-five treatments once a week showed 52.5% improvement in PASI score with one patient achieving clearance. Goldberg et al reported that all the 10 patients with PPP showed improvement between 50 and 100% with mean number of 11 sessions of 308-nm excimer laser [27]. No relapse was seen at the 3-month post-treatment, while relapse was seen in 60% of subjects at 6 months after treatment.…”
Section: Palmoplantar Psoriasis/pustulosismentioning
confidence: 91%
“…Hedef doku DNA olup, retiküler dermiste T-hücre apopitozunu tetiklemekte ve supraeritematojenik dozlarda uygulanabilmektedir 18 . Lokalize ve stabil psoriasis, palmoplantar psoriasis olgularında 308 nm excimer lazer etkili ve güvenilir bir tedavi metodu olarak düşünülebilir 19,20 . Tırnak psoriasisi üzerinde pulse dye lazer ile yapılan çalışmalarda; özellikle onikoliz, subungual keratoz üzerinde etkili olduğu, tırnak yatağında ve matriksinde düzelme sağlandığı gösterilmiştir.…”
Section: Psoriasisunclassified